Keterkaitan antara Konsumsi Pangan, Gaya Hidup, dan Status Gizi pada Pegawai Obes dan Normal - Lilik Kustiyah; Evy Damayanthi; Wilda Haerul Fazaarah; Cesilia Meti Dwiriani (Institut Pertanian Bogor, 2013)
The objective of this study was to analyze the interrelation between food consumption, energy and nutrients intake, lifestyle and socioeconomic status with nutritional status of employees. The observation was carried out on 73 employees of the Bogor Agricultural University, selected purposively. Design of this study was cross sectional. Data was collected by interview using questionnaire and measurement of body weight and height in order to get nutritional status of the subjects. Correlation Rank Spearman and Pearson was used to analyze correlation among 2 variables, and independent samples t-test was used to analyze differences between 2 nutritional status categories. The result showed that there was a significant difference (p<0.05) on gender, level of education, and nutrition knowledge between the samples of normal nutritional status and obesity. There was also significant and positive correlation between education level and the energy and carbohydrate intake; income of family with vitamin A and C intake; knowledge of nutrition with the intake of protein, fruit consumption habits and nutritional status. However, there was a significant and negative correlation between exercise habits with the fat intake.